PHYTOCHEMICAL SCREENING AND DPPH ANTIOXIDANT ACTIVITY OF Cleome viscosa FRACTIONS, A TRADITIONAL MEDICINAL PLANT FROM SOUTHEAST SULAWESI - Imran Imran; Nely Aryani Agusrini; Muh K. Natsir; Thamrin Azis; Alwahab Alwahab; Muh Edihar (UPT Publication and Journal Management, Islamic University of Kalimantan, 2026)
Cleome viscosa is a traditional medicinal plant known to contain bioactive antioxidant compounds. Accordingly, this study aimed to conduct phytochemical screening and evaluate the antioxidant activity of its methanolic extract and solvent fractions using the DPPH radical scavenging method. Extraction was performed by maceration with methanol, followed by liquid–liquid partitioning with n-hexane and ethyl acetate. Following extraction, phytochemical analysis indicated the presence of alkaloids, flavonoids, saponins, tannins, steroids, and terpenoids in the methanolic extract. To assess antioxidant potential, antioxidant activity was determined based on percentage inhibition at 517 nm, and IC50 values were calculated by linear regression. The results showed that ascorbic acid had very strong activity (IC50 = 3.86 ppm). In comparison, the ethyl acetate fraction exhibited strong antioxidant activity (IC50 = 29.25 ppm), while the n-hexane fraction showed weak activity (IC50 = 88.77 ppm). These findings suggest that semi-polar compounds contribute significantly to antioxidant potential.